Revitalization of Musyarakah Financing in BMT (Baitul Maal wat Tamwil) - Bayu Pratama, Muhamad Fajar; Mustafidah, Wiwit (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Musyarakah financing at Baitul Mal wat Tamwil (BMT) still faces a gap between product availability and effective implementation. This study aims to analyze the management of musyarakah financing and formulate its revitalization strategy at BMT UGT Capem Genteng, Banyuwangi. The study employs a qualitative approach with a single case study design. Data were collected through in-depth interviews with three key informants (branch head, head of financing department, and SME member) and direct observation. Data analysis used the interactive model of Miles, Huberman, and Saldaña. Findings indicate that musyarakah is in a state of administrative availability without effective realization. The main barriers are structurally twofold: from the members’ side (preference for fixed installments and mixed productive-consumptive use of funds) and from the institutional side (absence of business bookkeeping, moral hazard, technological limitations, and weak human resource competency). This study formulates the Four Pillar Revitalization Model (MR4P) encompassing education and hybrid musyarakah product innovation, strengthening of governance and risk management, digital technology optimization, and HR capacity building based on maqashid syariah values.